PRELIMINARY STUDY OF MICROSTRUCTURE DEPENDENCE OF MAGNETORESISTANCE BEHAVIOR ON Sm.-xLaxMo2Ge2 COMPOUND WITH X=O,l-o,3 - Setyo Purwanto; Wagiyo Wagiyo; M. Danil; Wisnu A.A; Rifai R. Muslich; Yasuo Yamaguchi; H. Yamauchi (PTBIN-BATAN)
AbstractPRELIMINARY STUDY OF MICROSTRUCTURE DEPENDENCE OF MAGNETORESISTANCE BEHAVIORON SmI. ' La , Mn 2G e 2 COMPOUND WITH x=O.l–O.3. We present the microstructure dependence of magnetoresistancebehavior in Sml.,La,Mn2Ge2 compound with x=0.1 0.3. We found that in bulk samples after milling and cold pressingP=10 tonlcm2 the magnetoresistance properties have improved from 0.6% to almost 7% with the adding of La concentration10%,20% and 30%. The bulk samples were prepared by tri arc melting, melted 4-5 times with the Ti addition for oxygen getter.After that, the samples were annealed for 96 hours at 900 °C at the vaccum furnace to make a good homogeneity. X -ray diffractionmeasurement was done using Cu target then the data was refined by Rietan software. Scanning electron micrograph data a pelletsamp.lesw ere taken by SEM 515 from Phillips company with two thousands magnification and operation power 20keV. Fromthe micrograph results, it was shown that the granular diameter increases with the Lanthanum content. In this preliminary studywe can conclude the magnetoresistance behavior is related to the density of samples and also to the fraction of primary phase ofSm La Mn Ge Analysis on this magnetoresistance behavior with magnetic granular solid model can help understanding this I- x x 2 2phenomenon.ABSTRAKSTurn PENDAHULUAN HUBUNGAN ANTARA MIKROSTRUKTUR DENGAN SIFAT MAGNETO RESISTANSIPADA Sml-lLa.Mn